Utility of Atherosclerosis Imaging in the Evaluation of High-Density Lipoprotein–Raising Therapies - Duivenvoorden, Raphaël (Current Science Inc., 2011)
Decreased level of high density-lipoprotein cholesterol (HDL-C) is a rigorous predictor for future cardiovascular events. Much effort is being made to develop HDL-C–raising pharmacotherapies in the attempt to avert the pandemic of atherosclerotic disease. Important properties by which HDL-C–raising compounds are effective involve improvement of cholesterol uptake from macrophages in plaque for transport back to the liver, improvement of endothelial function, and anti-inflammatory effects. Vascular imaging can aid in the determination which HDL-C–raising compounds are effective. Ultrasound and MRI have proved suitable for assessment of structural changes of the vessel wall. Ultrasound can also be used or assessment of endothelial function. 18F-fluordeoxyglucose positron emission tomography has opened up the possibility to assess vessel wall inflammation. In this article we discuss these various imaging techniques and how they can assess efficacy as well as provide pathophysiologic information on the mechanism of action of novel HDL-C–raising drugs.